Penggunaan Metode Pembelajaran Simulasi Untuk Materi Kesiapsiagaan Bencana Gempa Bumi Siswa Kelas X IIS Di SMA Negeri 1 Tawangsari Kabupaten Sukoharjo Tahun Ajaran 2015/2016 - Nurjanah, Ika Siti; , M. Amin Sunarhadi, S.Si., M.P (2015)
Data index single hazard prone districts / cities Sukoharjo occupied the national rangkin to 41 with a score of 47 and included into the high class. Subdistrict Tawangsari included in Sukoharjo district. According to the handbook of natural hazard risk analysis department of energy and mineral resources has a severe impact Tawangsari earthquake in the high category. Given districts Tawangsari an area that has high earthquake potential then in learning in school with regard to the achievement of KD 47 KD3.7 and the researchers used a simulation study model earthquake. Therefore, the simulation model tested on students in learning. The purpose of this research is 1) To determine the level of preparedness of students before the use of learning methods simulating earthquake Geography class X IIS in SMA N 1 Tawangsari 2) To determine the level of preparedness of students after the use of learning methods simulating earthquake Geography class X IIS in SMA N 1 Tawangsari. This study uses a quantitative research methods deskripstif. The research was one in SMA N 1 Tawangsari. The technique of collecting data using questionnaires. The results showed that the level of preparedness prior to the use of learning methods simulating earthquake is 67.06. The level of preparedness after learning method uses simulated earthquake was 83.43.